2017
DOI: 10.5101/nbe.v9i3.p191-198
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Fibroblasts Outgrowth onto Polycaprolactone Nanofibrous Grafted by Laminin Protein Using Carbon Dioxide Plasma Treatment

Abstract: A common approach in tissue engineering is to mimic the architecture of the natural extracellular matrix (ECM). The ECM plays an important role in regulating cellular behaviors by influencing cells with biochemical signals and topographical cues. Nanofibrous constructs have been used extensively as potential tissue engineering platforms. It is generally hypothesized that a close imitation of the ECM will provide a more conducive environment for cellular functions ranging from adhesion, migration, proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The subsequent dip coating in a laminin solution resulted in a further decrease in WCA value down to 30 • . Similar as the previously mentioned studies, the adsorbed laminin was found to be responsible for significantly improved fibroblast viability compared to the plasma-treated electrospun PCL scaffold [286].…”
Section: Protein Immobilization or Adsorption On Plasma-activated Nansupporting
confidence: 85%
See 2 more Smart Citations
“…The subsequent dip coating in a laminin solution resulted in a further decrease in WCA value down to 30 • . Similar as the previously mentioned studies, the adsorbed laminin was found to be responsible for significantly improved fibroblast viability compared to the plasma-treated electrospun PCL scaffold [286].…”
Section: Protein Immobilization or Adsorption On Plasma-activated Nansupporting
confidence: 85%
“…In contrast, a longer treatment time of 7 min resulted in less efficient heparin grafting. In a more recent study by Sahebalzamani et al, laminin has been physically adsorbed on CO 2 plasma-treated electrospun PCL scaffolds [286]. The conducted plasma treatment led to a reduction of the WCA value from 112 • to 67 • due to the introduction of oxygen-containing functionalities.…”
Section: Protein Immobilization or Adsorption On Plasma-activated Nanmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the most suitable and widely used techniques to achieve this goal is via plasma activation, which is known to introduce polar functional surface groups such as hydroxyls, carboxylic acids, amino groups, etc. [6,7,21,22,23,24]. Furthermore, this technique does not alter the morphology and bulk properties of the NF samples and typically greatly enhances surface biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Increased expression in wound bed region in mice [172]. Enhanced adhesion, growth, and viability in plasma-treated LM-modified PCL* [173] ONOOH and HOCl induce nitration, oxidation, and chlorination of LM residues [174][175][176]. Modification of self-polymerization and cell adhesion sites, which modulates the ECM structure…”
Section: Acellular Components Of the Tumour Microenvironmentmentioning
confidence: 99%